Detect of the eggs of P. equorum in the feces of horses by traditional method and molecular techniques in Baghdad, Iraq - Suha T. Al-Biatee; Balkes F. Hade; Haider M. Al-Rubaie (Iraqi Journal of Veterinary Sciences, 2024)
The risk of P. equorum infection in horses remains critical. Little studies were conducted to investigate prevalence and molecular analysis of P. equorum in Baghdad city, Iraq. In this study traditional detection followed by molecular technique depending on ITS-2 region were used as an attempt to evaluate this nuclear region as a genetic marker to diagnose the parasitic infection. One hundred and thirty-eight fecal samples of horses were collected and examined by direct wet mount smears, floatation method by NaCl. Extraction of genomic material, nested PCR was done followed by phylogenic analysis depending on ITS-2 region performed for the first time in Iraq and genetic substitutions to analyze Iraqi horses. Nested PCR were done after determining the total infection rate 6.52% by conventional technique, including 3.84% in males and 10% in females with significant difference. Highly infection rate 11.42% was recorded in the age group under 2 years and the lower infection rate 4% was found in the age group between 2-4 years with significant difference. The Iraqi isolates were recorded in the Gen Bank under the accession numbers MZ400507.1, MZ400508.1, MZ400509.1, and MZ4005010.1; while, phylogenetic analysis recorded an identity range between 97-100% with China, Australia and USA isolates. P. equorum is more distributed in younger horses than elderly in Baghdad city and ITS-2 region is a certain molecular marker for detection P. equorum isolates in Iraqi horses.